Pengembangan multimedia interaktif berbasis articulate storyline pada pembelajaran ekologi SMA kelas X - Alfin Amanatus Sa'adah; Puguh Karyanto; Nurmiyati Nurmiyati (Universitas Sebelas Maret, 2023)
ENThis study aims to: (1) develop an interactive multimedia based on articulate storylines at ecology learning for class X high school. ; (2) to test the feasibility of an interactive multimedia based on articulate storylines at ecology learning for class X high school. This research is a Research and Development (R&D) with a Four-D Models (4D) by Thiagarajan, in this study was modified into Three-D Models (3D). The data collection technique was carried out by questionnaire. The data analysis technique used is descriptive analysis. The results of research and development showed the characteristics of interactive multimedia based on articulate storylines are having interactive media, independent media, and deepening of ecological concepts. The characteristics of interactive multimedia based on articulate storylines that facilitate learning about population ecology, community ecology, and ecosystem ecology. The feasibility of the media showed an assesment of 89% from media experts, 89% from learning experts, 92% from practitioner/teacher responses and 95% from student responses. It was concluded that the media was suitable to be used as a medium for learning biology in the KD 3.10 class X ecology material. IDPenelitian ini bertujuan untuk : (1) mengembangkan multimedia interaktif berbasis articulate storyline pada pembelajaran ekologi SMA kelas X. ; (2) menguji kelayakan multimedia interaktif berbasis articulate storyline pada pembelajaran ekologi SMA kelas X. Penelitian ini merupakan penelitian Research and Development (R&D) dengan Four-D Models (4D) yang dikembangkan oleh Thiagarajan, dalam penelitian ini dimodifikasi menjadi Three-D Models (3D). Teknik pengumpulan data dilakukan dengan kuesioner. Teknik analisis data yang digunakan yaitu analisis data secara deskriptif. Hasil penelitian dan pengembangan menunjukkan karakteristik multimedia interaktif berbasis articulate storyline ekologi, yaitu memiliki media bersifat interaktif, media bersifat mandiri dan pendalaman konsep ekologi. Karakteristik multimedia interaktif berbasis articulate storyline ekologi memfasilitasi pembelajaran ekologi populasi, ekologi komunitas, dan ekologi ekosistem. Kelayakan media menunjukkan penilaian sebesar 89% dari ahli media, 89% dari ahli pembelajaran, 92% dari respon praktisi/ guru dan 95% dari respon siswa. Disimpulkan bahwa media layak digunakan sebagai media pembelajaran biologi pada materi ekologi KD 3.10 kelas X.